Analysis of Sedimentary Cyclicity Based on X-ray CT Images and Ultrasonic Measurements of Core Samples - Grochau, M.; Campos, E.; Mueller, T.; Nadri, D.; Clennell, B.; Gurevich, Boris (EAGE, 2010)
We present a methodology to assess rock properties by using X-ray computed tomography (CT) images along with the ultrasonic P-wave velocity measurements in laboratory under different confining pressures, and borehole logs from a stratigraphic interval in Campos Basin, offshore Brazil. The higher resolution of sampling in the core data overcomes the aliasing and smoothing effect of log-based measurements and enables the delineation of stratigraphic cycles. In addition, we observe a good correlation between X-ray CT value and ultrasonic P-wave velocity. Large variation in measured ultrasonic P-wave velocity between different samples is related to variations in calcium content.This improved understanding of the cyclic nature of physical property variations may help to correlate stratigraphy between wells and provide valuable information for paleo-climate studies. This study also helps to understand the facies heterogeneity in fine scale which is needed for choosing the correct rock physics model for further undergoing studies such as time lapse in this field. Given the periodic nature of sedimentary facies, the unique combination of X-ray CT images, ultrasonic P-wave velocities, and high resolution well logs in this field could be used as an example for seismic wave propagation studies in periodic media.